Zagadka "Ucieczki" = The riddle of "Escape" - Libera, Leszek (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This sketch has failed to solve the puzzle of "Escape" ["Ucieczka"]. Three basic interrelated questions about the time and place of the work's origin and its message effectively defend themselves against a clear and convincing answer. One cannot exclude the probability of any of the presented hypotheses as to the time and place of the work's origin. What was Mickiewicz's purpose while writing and publishing this ballad still remains the mystery the poet took to his grave. The attempts to categorize "Escape" as an experiment (as Kleiner wants) or a poetry workshop exercise (Maria Żmigrodzka) are rather a testimony of surrender to the text, which - referring indirectly to Bürger's original - is nothing but a Polish version of "Lenora", like "Świetlana" by Żukowski is its Russian version. However, being taken out of the volume "Ballady i romanse" of 1822 it gives the impression of an oddly isolated work.
Keywords: Mickiewicz, Adam (1798-1855); Bürger, Gottfried August (poeta niemiecki; 1747-1794); "Lenora"; "Ucieczka"; ballada; "Escape"; ballade